РАДИОНУКЛИД 7ВЕ В МЕСЯЧНЫХ 2018 ГОДА И ЛЕТНЕ-ОСЕННИХ АТМОСФЕРНЫХ ВЫПАДЕНИЯХ 2019 ГОДА В ГОРОДЕ ТАШКЕНТЕ - Базарбаев, Н.Н.; Эшназаров, А.И.; Махмудов, С.К.; Холбаев, И.; Чиндалиев, М.Х.; Холов, Д.М. (SCIENCE and SOCIETY, 2020)
The gamma-spectrometric method was used to study the activity of the cosmogenic7Be radionuclide in monthly atmospheric deposition in 2018 in Tashkent. The measurement results are compared with the monthly values of wet precipitation, temperature, humidity and dustiness of the air.
Keywords: natural radionuclides; specific activity; effective activity; permanent observation points; grading; assessment specific total activity; radioactive equilibrium